Viabilidade de um processo de vigilância tecnológica através do estágio supervisionado, visando à transferência de tecnologia - Gandolfo, Celso Aparecido (2006)
The challenge of this century is motivate and firm changes of behavior that allow the conduction, the so longed partnership and cooperation among college education institutions and the productive way. The peculiarities experienced by the productive segments are not applicable exclusively to their industrial segments. The college education institution, inserted in the society, is also called to rethink the phenomenon of the work and to insert the teaching/learning process in this new context. Thus, the present work analyze the viability of a technological vigilance process through the supervised apprenticeship aiming the technology transfer. This analysis has as characteristic the exploratory factor through the technical procedure of case study. It will look for the understanding of the general nature of the problem and of the current situation of how the use of the information and knowledge generated from the apprenticeship happens. The presented methodology will allow identify ideas and signs of as they are conceived the information looked for of the context managerial, of the perceptions and understanding of each one of the collaborators directly involved in the context university-company and technology transfer looking for as result the lifted up hypothesis through the contributions supplied by the questionnaire and researches applied. The conclusion of the work is based on the analysis of this viability, with the purpose of technological updating. Positive aspects are also evidenced heading for that viability, aiming to arouse on the potential of the information originated from the apprenticeship activity, a rich source of technological updating and conversion of the knowledge in UTFPR-CM through the proposed process.